HUBUNGAN KONSEP DIRI DAN MOTIVASI BERPRESTASI DENGAN HASIL BELAJAR MAHASISWA STKIP HAMZANWADI SELONG PROGRAM STUDI PENDIDIKAN GEOGRAFI TAHUN AKADEMIK 2015/2016 - Sri Agustina; Tuti Mutia (Universitas Hamzanwadi, 2015)
This study aims to determine whether there is a relationship between self-concept and achievement motivation and academic achievement of students of Geography Education. This study uses a quantitative approach to research that the data in the form of numbers, or qualitative data diangkakan (Sugiyono, 2005: 13), while the method used in this research is to use the correlation method. The population in this study were all students of geography education. This study aims to determine the relationship between self-concept (X1) and achievement motivation (X2) with student learning outcomes (Y). Then the tool used to collect data were questionnaires and documentation. Results of analysis using the Correlation showed that: (1) there is a positive and significant relationship between self concept with student results STKIP Hamzanwadi Selong Geography Education courses Academic Year 2014/2015; (2) there is a positive and significant relationship between achievement motivation and student learning outcomes STKIP Hamzanwadi Selong Geography Education courses Academic Year 2014/2015; (3) there is a positive and significant relationship between self-concept and achievement motivation and learning outcomes STKIP Hamzanwadi Selong Geography Education courses for academic year 2014/2015. Keywords: Self-concept, Achievement Motivation, Learning Outcomes